Protective effects of betaglucin on myocardial tissue during myocardial infarction in rats and dogs - Qian, Jiao; Liu, Ai-jun; Zhang, Wei; Wen, Zhi-peng; Lin, Li-li; Wang, Jing-hang; Su, Ding-feng; Liu, Jian-guo (Acta pharmacologica Sinica, 2009)
Aim： To test the protective effects of betaglucin, a novel beta-glucan, on models of myocardial infarction （MI） in rats and dogs. Methods： The left anterior descending （LAD） coronary artery occlusion model was used to induce an MI in rats and dogs. Three doses of betaglucin （10, 30 and 100 mg/kg）, propranolol （positive control, 1 mg/kg） and vehicle alone （5% glucose solution） were administered before LAD occlusion, and characteristics of the resulting MI were subsequently assessed. In anesthetized dogs, blood pressure heart rate, ventricular function, coronary artery blood flow and myocardial oxygen consumption were determined before and after the drug administration. Results： The MI mass in both rats and dogs was significantly reduced by betaglucin （30 and 100 mg/kg, P〈O.01） and propranolol （P〈O.01）. In anesthetized dogs, coronary artery blood flow was increased significantly by betaglucin （30 and 100 mg/kg, P〈O.01）, but blood pressure, heart rate and ventricular function were not changed （P〉O.05）. High-dose betaglucin （100 mg/kg） increased myocardial oxygen consumption, but not to a statistically significant level （P〉O.05）. The hemodynamic indexes were significantly changed by propranolol. Conclusion： Betaglucin has protective effects on myocardial tissue during MI in rats and dogs and has no influence on hemodynamic parameters at a therapeutic dose. The increase in coronary artery blood flow induced by betaglucin might be beneficial in the treatment of patients with MI.